Response of Soil Chemical Properties to Irrigation with Winery Wastewater on a Well-drained Sandy Soil - Mulidzi, A.R.; Clarke, C.E.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2019)
Most wineries in South Africa dispose of their wastewater through land application. This is carried out by irrigating small areas of cultivated pasture with the wastewater or ponding, with the former being the more general practice. Land application of winery wastewater results in the accumulation of potassium (K+) and sodium (Na+) in the soil and leaching of calcium (Ca2+) and magnesium (Mg2+).This could lead to long term instability of soil structure. The objective of this study was to investigate the effect of irrigation with winery wastewater on chemical soil properties and potential environmental impacts. Therefore, an existing grazing paddock at a winery near Rawsonville was selected where wastewater had been applied for many years. Due to the high volumes of wastewater irrigation plus rainfall, the inevitable over-irrigation leached large amounts of cations, particular K+ and Na+, beyond 90 cm soil depth at the selected study site. These leached elements are likely to end up in natural water resources in the long run. Irrigation with winery wastewater did not have a pronounced effect on soil pH(KCl). This was probably due to the decomposition of organic matter, and the fact that the applied salts were leached beyond 90 cm depth. The study confirmed that disposal of winery wastewater through land application can only be recommended where wastewater application will not exceed the water requirement of the crop as well as the water holding capacity of the soil which is being irrigated.